Electrolyte additive, electrolyte and application
By using sulfonic acid electrolyte additives such as sodium benzenesulfonate and sodium pyridine-3-sulfonate in aqueous zinc ion batteries, an adsorption layer is formed to inhibit dendrite generation and water molecules decomposition, the electrodes in aqueous zinc ion batteries are solved. The problems of lateral water molecules decomposition and dendrites improve the cycle stability and reversibility of the battery.
Patent Information
- Application Number
- CN202411604790.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
AI Technical Summary
There are problems in the decomposition of water molecules on the electrode side and dendrite generation in the aqueous zinc ion battery, which leads to low reversibility and cyclic stability, limiting its practical application.
Sodium benzenesulfonate, sodium 1-hexanesulfonate or sodium pyridine-3-sulfonate are used as electrolyte additives. The thionyl group of these additives has a strong coordination effect with zinc atoms to form an adsorption layer and inhibit zinc ions. uneven deposition and dendrites.
It effectively inhibits the two-dimensional diffusion of zinc surface, promotes three-dimensional diffusion, reduces the generation of dendrites and by-products, improves the cyclic stability of zinc negative electrodes, and reduces the decomposition of water molecules, and improves the reversibility of the battery.
Smart Images

Figure CN119447512A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion batteries, and in particular to an electrolyte additive, an electrolyte and applications. Background Art
[0002] Secondary batteries are an important class of chemical energy storage devices, and lithium-ion batteries have attracted much attention due to their high energy density. However, the scarcity of lithium metal resources, safety issues of lithium anodes, and flammability of organic electrolytes lead to high cost and low safety, which hinders their widespread application in large-scale energy storage networks. Therefore, aqueous rechargeable batteries have attracted increasing attention from researchers due to their advantages of low cost, environmental protection, and high safety. Among various aqueous batteries, aqueous zinc-ion batteries (ZIBs) have attracted much attention due to their abundant resources and high theoretical capacity (820mAh g -1 ), low redox potential (-0.763 V vs standard hydrogen electrode), and high safety and ionic conductivity of aqueous electrolytes ensure its prospects for large-scale application.
[0003] At present, the application of aqueous zinc-ion batteries still faces challenges. Dendrite growth on the zinc anode surface, corrosion caused by H2O decomposition, hydrogen evolution, and byproducts such as Zn4SO4(OH)6·nH2O seriously reduce the reversibility and cycle stability of ZIBs, thereby limiting the practical application of ZIBs. At present, some studies have carried out a lot of research work on the above-mentioned problems, mainly including two strategies: zinc negative electrode interface modification and electrolyte optimization. The negative electrode interface modification is to separate the negative electrode surface from water molecules by constructing a modified layer on the negative electrode surface in situ or ex situ, thereby reducing the decomposition of water molecules on the negative electrode surface and reducing the local current density, promoting the uniform deposition of zinc ions. However, due to the continuous change in the volume of zinc metal during the electroplating stripping process, the modified layer falls off because it cannot continue to withstand the volume change during the charge and discharge process. In contrast, electrolyte optimization is considered to be the most feasible strategy due to its simple preparation process and low cost. In this context, various methods with optimized Zn 2+ Electrolyte additives that coordinate the environment and modify the electrolyte / electrode interface function. Given the complexity of the problems existing in aqueous zinc-ion batteries, reducing the decomposition of water molecules on the electrode side is the key to achieving the rapid development of aqueous zinc-ion batteries. At present, some studies are devoted to simply regulating the behavior of water molecules on the negative electrode surface from the direction of the electrolyte or the electrode surface. However, the effect of using additives to solve the problem of water molecule decomposition reported so far is poor.
[0004] Therefore, how to solve the problem of water molecule decomposition plays a key role in the widespread application of aqueous zinc-ion batteries. Summary of the invention
[0005] The purpose of the present invention is to provide an electrolyte additive, an electrolyte and an application thereof, so as to solve the problems of water molecule decomposition and dendrite generation on the electrode side of the existing aqueous zinc ion battery.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides an electrolyte additive, which is one or more of sodium benzenesulfonate, sodium 1-hexanesulfonate and sodium pyridine-3-sulfonate.
[0008] The present invention also provides an electrolyte containing the above electrolyte additive, wherein the electrolyte comprises the following components:
[0009] Electrolytes, electrolyte additives, water.
[0010] In the above electrolyte, the concentration of the electrolyte additive in the electrolyte is 0.01-2 mol / L.
[0011] In the above electrolyte, the concentration of the electrolyte in the electrolyte is 1 to 3 mol / L.
[0012] In the above-mentioned electrolyte, the electrolyte is a soluble zinc salt.
[0013] In the above electrolyte, the soluble zinc salt is one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc perchlorate and zinc nitrate.
[0014] The invention also provides an application of an electrolyte in an aqueous zinc ion battery.
[0015] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) The present invention uses sulfonic acid organic additives. The rich sulfinyl groups in sodium benzenesulfonate, sodium 1-hexanesulfonate, and sodium pyridine-3-sulfonate enable strong coordination between zinc atoms and additive molecules due to the lone pair of electrons of the sulfur atom therein. The additive molecules are preferentially adsorbed on the negative electrode interface in a chemical adsorption manner and form an adsorption layer in situ on the zinc surface. The adsorption layer can effectively inhibit the two-dimensional diffusion of the Zn surface and promote three-dimensional diffusion, thereby inhibiting the uneven deposition of zinc ions and the generation of dendrites. In addition, the adsorption layer can separate H2O from the Zn anode and occupy the decomposition site of active water molecules, thereby inhibiting interface side reactions (HER, corrosion, and byproducts, etc.).
[0017] (2) Sodium pyridine-3-sulfonate with a high donor number can preferentially coordinate with zinc ions through the pyridine ring and exclude part of the solvated H2O. Together with the adsorption layer formed by the sulfinyl group adsorbed on the zinc surface, it inhibits the decomposition of H2O and the formation of dendrites, effectively improving the cycle stability of the zinc negative electrode.
[0018] (3) The aqueous zinc ion battery electrolyte additive of the present invention has a simple electrolyte process, high controllability, low cost, and strong industrial applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.
[0020] Figure 1 For comparison, the Zn||Zn symmetric battery in Application Example 1 at a current density of 2 mA / cm 2 , surface capacity is 2mAh / cm 2 SEM image of zinc deposits after 20 cycles under the same conditions;
[0021] Figure 2 For the Zn||Zn symmetric battery in Application Example 1, the current density is 2 mA / cm 2 , surface capacity is 2mAh / cm 2 SEM image of zinc deposits after 20 cycles under the same conditions;
[0022] Figure 3 For the Zn||Zn symmetric battery in Application Example 2, the current density is 2 mA / cm 2 , surface capacity is 2mAh / cm 2 SEM image of zinc deposits after 20 cycles under the same conditions;
[0023] Figure 4 For the Zn||Zn symmetric battery in Application Example 3, the current density is 2 mA / cm 2 , surface capacity is 2mAh / cm 2 SEM image of zinc deposits after 20 cycles under the same conditions;
[0024] Figure 5 The Zn||Zn symmetric battery in Application Examples 1 to 3 and Comparative Application Example 1 is subjected to a current density of 5 mA / cm 2 , surface capacity is 2mAh / cm 2 Constant current cycle test diagram under conditions;
[0025] Figure 6 After adding different concentrations of sodium pyridine-3-sulfonate in application examples 3 to 6 and comparative application example 1, the Zn||Zn symmetric battery at a current density of 4 mA / cm2 , surface capacity is 4mAh / cm 2 Constant current cycle test diagram under conditions;
[0026] Figure 7 The Zn||Zn symmetrical battery in Application Examples 1 to 3 and Comparative Application Example 1 was discharged at a depth of 39% and a current density of 20 mA / cm 2 , surface capacity is 20mAh / cm 2 Constant current cycle test diagram under . DETAILED DESCRIPTION
[0027] The present invention provides an electrolyte additive, which is preferably one or more of sodium benzenesulfonate, sodium 1-hexanesulfonate, and sodium pyridine-3-sulfonate, further preferably sodium benzenesulfonate or sodium pyridine-3-sulfonate, and more preferably sodium pyridine-3-sulfonate.
[0028] The present invention also provides an electrolyte containing the above electrolyte additive, wherein the electrolyte comprises the following components:
[0029] Electrolytes, electrolyte additives, water.
[0030] In the above electrolyte, the concentration of the electrolyte additive in the electrolyte is preferably 0.01 to 2 mol / L, more preferably 0.05 to 0.2 mol / L, and more preferably 0.05 mol / L.
[0031] In the above-mentioned electrolyte, the concentration of the electrolyte in the electrolyte is preferably 1 to 3 mol / L, more preferably 2 to 3 mol / L, and more preferably 2 mol / L.
[0032] In the above-mentioned electrolyte, the electrolyte is preferably a soluble zinc salt.
[0033] In the above-mentioned electrolyte, the soluble zinc salt is preferably one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc perchlorate, and zinc nitrate, further preferably one or more of zinc sulfate, zinc perchlorate, and zinc nitrate, and more preferably zinc sulfate.
[0034] The invention also provides an application of an electrolyte in an aqueous zinc ion battery.
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] This embodiment provides an aqueous zinc ion battery electrolyte containing a sulfonic acid additive, and the preparation method thereof comprises the following steps:
[0038] (1) Weigh 5.75 g of ZnSO4·7H2O and add it to 7.5 mL of deionized water. Stir thoroughly until it is completely dissolved to obtain a zinc sulfate solution with a concentration of 2 mol / L.
[0039] (2) Weigh 0.09 g of sodium benzenesulfonate powder, add it to the zinc sulfate solution, and stir thoroughly until it is completely dissolved to obtain an electrolyte containing 0.05 mol / L of sodium benzenesulfonate additive.
[0040] Example 2
[0041] This embodiment provides an aqueous zinc ion battery electrolyte containing a sulfonic acid additive, and the preparation method thereof comprises the following steps:
[0042] (1) Weigh 5.75 g of ZnSO4·7H2O and add it to 7.5 mL of deionized water. Stir thoroughly until it is completely dissolved to obtain a zinc sulfate solution with a concentration of 2 mol / L.
[0043] (2) Weigh 0.094 g of sodium 1-hexane sulfonate powder, add it to the zinc sulfate solution, and stir thoroughly until it is completely dissolved to obtain an electrolyte containing 0.05 mol / L of sodium 1-hexane sulfonate additive.
[0044] Example 3
[0045] This embodiment provides an aqueous zinc ion battery electrolyte containing a sulfonic acid additive, and the preparation method thereof comprises the following steps:
[0046] (1) Weigh 5.75 g of ZnSO4·7H2O and add it to 7.5 mL of deionized water. Stir thoroughly until it is completely dissolved to obtain a zinc sulfate solution with a concentration of 2 mol / L.
[0047] (2) Weigh 0.09 g of sodium pyridine-3-sulfonate powder, add it to the zinc sulfate solution, and stir thoroughly until it is completely dissolved to obtain an electrolyte containing 0.05 mol / L of sodium pyridine-3-sulfonate additive.
[0048] Example 4
[0049] This embodiment provides an aqueous zinc ion battery electrolyte containing a sulfonic acid additive, and the preparation method thereof comprises the following steps:
[0050] (1) Weigh 5.75 g of ZnSO4·7H2O and add it to 7.5 mL of deionized water. Stir thoroughly until it is completely dissolved to obtain a zinc sulfate solution with a concentration of 2 mol / L.
[0051] (2) Weigh 0.018 g of sodium pyridine-3-sulfonate powder, add it to the zinc sulfate solution, and stir thoroughly until it is completely dissolved to obtain an electrolyte containing 0.01 mol / L of sodium pyridine-3-sulfonate additive.
[0052] Example 5
[0053] This embodiment provides an aqueous zinc ion battery electrolyte containing a sulfonic acid additive, and the preparation method thereof comprises the following steps:
[0054] (1) Weigh 5.75 g of ZnSO4·7H2O and add it to 7.5 mL of deionized water. Stir thoroughly until it is completely dissolved to obtain a zinc sulfate solution with a concentration of 2 mol / L.
[0055] (2) Weigh 0.18 g of sodium pyridine-3-sulfonate powder, add it to the zinc sulfate solution, and stir thoroughly until it is completely dissolved to obtain an electrolyte containing 0.1 mol / L of sodium pyridine-3-sulfonate additive.
[0056] Example 6
[0057] This embodiment provides an aqueous zinc ion battery electrolyte containing a sulfonic acid additive, and the preparation method thereof comprises the following steps:
[0058] (1) Weigh 5.75 g of ZnSO4·7H2O and add it to 7.5 mL of deionized water. Stir thoroughly until it is completely dissolved to obtain a zinc sulfate solution with a concentration of 2 mol / L.
[0059] (2) Weigh 0.36 g of sodium pyridine-3-sulfonate powder, add it to the zinc sulfate solution, and stir thoroughly until it is completely dissolved to obtain an electrolyte containing 0.2 mol / L of sodium pyridine-3-sulfonate additive.
[0060] Comparative Example 1
[0061] This comparative example provides an aqueous zinc ion battery electrolyte, and the preparation method thereof comprises the following steps:
[0062] Weigh 5.75 g of ZnSO4·7H2O and add it to 7.5 mL of deionized water. Stir thoroughly until it is completely dissolved to obtain a zinc sulfate solution with a concentration of 2 mol / L, which is the aqueous zinc ion battery electrolyte.
[0063] Application Example 1
[0064] Preparation of Zn||Zn symmetric battery: Cut zinc foil into discs with diameters of 12 mm and 16 mm, then ultrasonically clean the discs with deionized water and anhydrous ethanol for 3 times, 10 min each time, and then put them into an oven for drying for 1 h to obtain zinc electrode plates. Use a commercial CR2032 electrode shell, drop 150 μL of the electrolyte containing 0.05 mol / L sodium benzenesulfonate additive in Example 1 on the diaphragm, assemble the battery in the order of positive electrode shell-zinc foil-diaphragm-electrolyte-zinc foil-spring-gasket-negative electrode shell, and pressurize and package after assembly to prepare a Zn||Zn symmetric battery.
[0065] Application Example 2
[0066] A Zn||Zn symmetrical battery was prepared, as shown in Application Example 1, except that the electrolyte containing 0.05 mol / L sodium benzenesulfonate additive in Example 1 was replaced with the electrolyte containing 0.05 mol / L sodium 1-hexanesulfonate additive in Example 2.
[0067] Application Example 3
[0068] A Zn||Zn symmetrical battery was prepared, as shown in Application Example 1, except that the electrolyte containing 0.05 mol / L sodium benzenesulfonate additive in Example 1 was replaced with the electrolyte containing 0.05 mol / L sodium pyridine-3-sulfonate additive in Example 3.
[0069] Application Example 4
[0070] A Zn||Zn symmetrical battery was prepared, as shown in Application Example 1, except that the electrolyte containing 0.05 mol / L sodium benzenesulfonate additive in Example 1 was replaced by the electrolyte containing 0.01 mol / L sodium pyridine-3-sulfonate additive in Example 4.
[0071] Application Example 5
[0072] A Zn||Zn symmetrical battery was prepared, as shown in Application Example 1, except that the electrolyte containing 0.05 mol / L sodium benzenesulfonate additive in Example 1 was replaced by the electrolyte containing 0.1 mol / L sodium pyridine-3-sulfonate additive in Example 5.
[0073] Application Example 6
[0074] A Zn||Zn symmetrical battery was prepared, as shown in Application Example 1, except that the electrolyte containing 0.05 mol / L sodium benzenesulfonate additive in Example 1 was replaced by the electrolyte containing 0.2 mol / L sodium pyridine-3-sulfonate additive in Example 6.
[0075] Comparative application example 1
[0076] A Zn||Zn symmetrical battery was prepared, as shown in Application Example 1, except that the electrolyte containing 0.05 mol / L sodium benzenesulfonate additive in Example 1 was replaced with the 2 mol / L zinc sulfate solution in Comparative Example 1.
[0077] The Zn||Zn symmetrical battery prepared above was subjected to constant current charge and discharge test with a current density of 5-20 mA / cm 2 , surface capacity is 2~20mAh / cm 2 .
[0078] Figure 1 to Figure 4 The Zn||Zn symmetric battery in Application Examples 1 to 3 and Comparative Application Example 1 is subjected to a current density of 2 mA / cm 2 , surface capacity is 2mAh / cm 2 SEM image of zinc deposits after 20 cycles under the same conditions. Figure 1 It can be seen that the surface of the Zn plate is rough after 20 cycles in the ZnSO4 electrolyte of comparative application example 1, indicating uneven deposition, while the surface of the Zn sheet circulating in the sulfonic acid electrolyte is relatively smooth, indicating that the deposition of the zinc sheet is more uniform and dense after adding the sulfonic acid additive. The electrolyte with the sodium pyridine-3-sulfonate additive shows the smoothest and most uniform morphology, indicating that the formation of dendrites and by-products can be more effectively suppressed under the dual effects of electrolyte desolvation and electrode surface adsorption layer.
[0079] Figure 5 The Zn||Zn symmetric battery in Application Examples 1 to 3 and Comparative Application Example 1 is subjected to a current density of 5 mA / cm 2 , surface capacity is 2mAh / cm 2 Constant current cycle test diagram under the conditions. Figure 5 As shown in the figure, after adding sodium pyridine-3-sulfonate additive, the Zn||Zn symmetric battery showed an ultra-long cycle life of 1400h, and the addition of sodium benzenesulfonate and sodium 1-hexanesulfonate could also stably cycle for 700h, while the comparative application example 1 short-circuited after only 330h of cycling. This shows that sodium pyridine-3-sulfonate showed better cycle stability under the synergistic effect of pyridine ring and sulfinyl group.
[0080] Figure 6 After adding different concentrations of sodium pyridine-3-sulfonate in application examples 3 to 6 and comparative application example 1, the Zn||Zn symmetric battery at a current density of 4 mA / cm 2 , surface capacity is 4mAh / cm 2 Constant current cycle test diagram under the conditions. Figure 6As shown in the figure, adding 0.05mol / L and 0.1mol / L sodium pyridine-3-sulfonate additives both stably cycled for 800h without short circuit, but adding 0.1mol / L sodium pyridine-3-sulfonate additives continued to increase the voltage hysteresis after 600h of cycling. On the contrary, adding 0.05mol / L sodium pyridine-3-sulfonate additives maintained an ultra-low voltage hysteresis of no more than 5mV within 800h. The Zn||Zn symmetric battery using 2mol / L zinc sulfate electrolyte shorted after only 50h of cycling.
[0081] Figure 7 The Zn||Zn symmetrical battery in Application Examples 1 to 3 and Comparative Application Example 1 was discharged at a depth of 39% and a current density of 20 mA / cm 2 , surface capacity is 20mAh / cm 2 Constant current cycle test diagram under the conditions. Figure 7 As shown in the figure, under this test condition, sodium benzenesulfonate and sodium 1-hexanesulfonate were stably cycled for 180h and 140h respectively, and sodium pyridine-3-sulfonate showed ultra-high cycle stability of more than 380h. However, comparative application example 1 was short-circuited after only 60h of cycling. This further shows that even under the test conditions of high discharge depth and high current density, sodium pyridine-3-sulfonate can still maintain more excellent cycle stability to achieve practical application goals.
[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrolyte additive, characterized in that: The electrolyte additive is one or more of sodium benzenesulfonate, sodium 1-hexanesulfonate, and sodium pyridine-3-sulfonate.
2. An electrolyte containing the electrolyte additive according to claim 1, characterized in that: The electrolyte comprises the following components: Electrolytes, electrolyte additives, water.
3. An electrolyte according to claim 2, characterized in that: The concentration of the electrolyte additive in the electrolyte is 0.01-2 mol / L.
4. An electrolyte according to claim 3, characterized in that: The concentration of the electrolyte in the electrolyte is 1-3 mol / L.
5. An electrolyte according to claim 4, characterized in that: The electrolyte is a soluble zinc salt.
6. An electrolyte according to claim 5, characterized in that: The soluble zinc salt is one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc perchlorate and zinc nitrate.
7. Use of an electrolyte according to any one of claims 2 to 6 in an aqueous zinc ion battery.